Photodissociation of aligned CH3I and C6H3F2I molecules probed with time-resolved Coulomb explosion imaging by site-selective extreme ultraviolet ionization - Amini, Kasra; Savelyev, Evgeny; Brauße, Felix; Berrah, Nora; Bomme, Cédric; Brouard, Mark; Burt, Michael; Christensen, Lauge; Düsterer, Stefan; Erk, Benjamin; Höppner, Hauke; Kierspel, Thomas; et al. (My University, 2018)
We explore time-resolved Coulomb explosion induced by intense, extreme ultraviolet (XUV) femtosecond pulses from a free-electron laser as a method to image photo-induced molecular dynamics in two molecules, iodomethane and 2,6-difluoroiodobenzene. At an excitation wavelength of 267 nm, the dominant reaction pathway in both molecules is neutral dissociation via cleavage of the carbon–iodine bond. This allows investigating the influence of the molecular environment on the absorption of an intense, femtosecond XUV pulse and the subsequent Coulomb explosion process. We find that the XUV probe pulse induces local inner-shell ionization of atomic iodine in dissociating iodomethane, in contrast to non-selective ionization of all photofragments in difluoroiodobenzene. The results reveal evidence of electron transfer from methyl and phenyl moieties to a multiply charged iodine ion. In addition, indications for ultrafast charge rearrangement on the phenyl radical are found, suggesting that time-resolved Coulomb explosion imaging is sensitive to the localization of charge in extended molecules.
Citation: Amini, K., Savelyev, E., Brauße, F., Berrah, N., Bomme, C., Brouard, M., … Boll, R. (2018). Photodissociation of aligned CH 3 I and C 6 H 3 F 2 I molecules probed with time-resolved Coulomb explosion imaging by site-selective extreme ultraviolet ionization. Structural Dynamics, 5(1), 014301. https://doi.org/10.1063/1.4998648
Keywords: Free electron lasers; Photodissociation; Photoionization; X-rays